Evaluation of the synthetic scope and the reaction pathways of proton-coupled electron transfer with redox-active guanidines in C−H activation processes - Wild, Ute; Walter, Petra; Hübner, Olaf; Kaifer, Elisabeth; Himmel, Hans-Jörg (Chemistry - a European journal, 2020)
Proton-coupled electron transfer (PCET) is currently intensively studied because of its importance in synthetic chemistry and biology. In recent years it was shown that redox-active guanidines are capable PCET reagents for the selective oxidation of organic molecules. In this work, the scope of their PCET reactivity regarding reactions that involve C−H activation is explored and kinetic studies carried out to disclose the reaction mechanisms. Organic molecules with potential up to 1.2 V vs. ferrocenium/ferrocene are efficiently oxidized. Reactions are initiated by electron transfer, followed by slow proton transfer from an electron-transfer equilibrium.
First published: 07 September 2020
Gesehen am 25.10.2021